Grado de satisfacción con simulación y prácticas docentes tradicionales en la adquisición de competencias clínicas en semiología cardiovascular en estudiantes de medicina de la Universidad Técnica Particular de Loja septiembre 2012-febrero 2013 - Benítez Hurtado, Mariana del Carmen (2014)
In order to compare two methods of teaching in medical students and teachers to acquire clinical competence in cardiovascular symptomatology this study was done in a descriptive, prospective, cross-sectional approach. The instrument employed was a survey of 52 students who received training using traditional methodology (Group A) and 64 students who received a workshop of simulation-based cardiovascular symptomatology (Group B). It was evidented in the group A a degree of satisfaction with a mean value of 3.00 categorized as "Unsatisfactory" on the Likert scale. The group B showed a mean value of 4.3 categorized as "Very satisfactory". Teachers showed a mean value of 3.45 giving equivalent Likert scale as "Unsatisfactory" with the traditional teaching method. Through simulation indicate an average value of 4.67 giving the equivalent as "Satisfactory". In conclusion cardiovascular symptomatology teaching through clinical simulation shows a high degree of satisfaction in both students and teachers in relation to the traditional methodology